Understanding women's magazines : publishing, markets and readerships - Gough-Yates, Anna, 1968- (Routledge, 2003)
Understanding Women's Magazines investigates the changing landscape of women's magazines. Anna Gough-Yates focuses on the successes, failures and shifting fortunes of a number of magazines including Elle, Marie Claire, Cosmopolitan, Frank, New Woman and Red and considers the dramatic developments that have taken place in women's magazine publishing in the last two decades. Understanding Women's Magazines examines the transformation in the production, advertising and marketing practices of women's magazines. Arguing that.